Study on the Performance of Signaled Intersections in the City of Bandar Lampung (Case Study of JL. Sultan Agung - Kimaja Intersection durig Covid-19 - Pramita, Galuh; Lestari, Fera; Bertarina, Bertarina (Fakultas Teknik Universitas Tanjungpura, 2020)
Transportation has a part important in supporting community activities in a country. The transportation problem in Indonesia is one that is difficult to handle. The city of Bandar Lampung has a congestion problem that occurs at signaled intersections. One of the Traffic congestion occurred at the Sultan Agung